Diversity and assembly of planktonic protist communities in the Jeju Strait, Korea - Min, Juhee; Kim, Kwang Young (Frontiers in Marine Science, 2023)
This study examined planktonic protists—microbial eukaryotes with cell sizes between 2 and 200 µm—to understand their diversity, assembly processes, and co-existence patterns in surface waters of the Jeju Strait (JS), Korea. Using small organelle-enriched metagenomics, the study identified 252 operational taxonomic units (OTUs) across three distinct oceanographic regions of the JS during multiple seasons. Interestingly, there were no significant variations in the diversity or phylogenetic structures of these planktonic protist communities (PPCs), indicating a uniform distribution of PPCs across the strait. However, a higher clustering of their phylogenetic structure was observed in November, implying that seasonal environmental factors influenced their assembly. The study also discovered that seasonal shifts had a major impact on the composition of these communities. For example, Myzozoa was more prevalent in March, while Ochrophyta dominated in November. Protist size also varied seasonally, with larger protists increasing from June to November and then decreasing by March. Neutral community model analysis provided insights into the role of stochastic processes in shaping community assembly. The majority of OTUs fell into the neutral category, while a smaller proportion displayed non-neutral patterns. For instance, certain species like Pseudo-nitzschia and Chaetoceros were frequently found but had lower abundance, while other species like Alexandrium and Protoceratium were less frequent but more abundant. The feeding patterns, or trophic modes, of these protists also showed variations. Additionally, the study unveiled a complex network of species interactions within the strait, including positive mutualistic relationships and negative competitive interactions. The intricate interaction network consisted of 61 distinct modules, suggesting the presence of specialized subgroups within the PPCs that fulfill unique ecological roles. These subgroups contribute significantly to the overall stability and resilience of the ecosystem.